2021
DOI: 10.1111/andr.13003
|View full text |Cite
|
Sign up to set email alerts
|

“Mask up to keep it up”: Preliminary evidence of the association between erectile dysfunction and COVID‐19

Abstract: Background: Erectile dysfunction (ED), as the hallmark of endothelial dysfunction, could be a short-or long-term complication of COVID-19. Additionally, being ED a clinical marker and predictor of non-communicable chronic diseases, particularly cardiovascular, subjects with ED could potentially have a higher risk of contracting COVID-19.Objectives: To investigate the prevalence of ED among subjects with a reported diagnosis of COVID-19 and to measure the association of COVID-19 and ED. Materials and methods:We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
83
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(97 citation statements)
references
References 76 publications
7
83
0
7
Order By: Relevance
“…As a matter of fact, it was reported that the prevalence of ED in COVID-19 patients was significantly higher. 52 At 6 months after acute infection with COVID-19, a certain proportion of recovered patients remained diffusion impairment, and patients who were more severely ill during their hospital stay had more severe impaired pulmonary diffusion capacities and abnormal chest imaging manifestation. 43 Therefore, it was likely that the erectile function in COVID-19 patients with a recovery time of 80 days was impaired.…”
Section: Discussionmentioning
confidence: 99%
“…As a matter of fact, it was reported that the prevalence of ED in COVID-19 patients was significantly higher. 52 At 6 months after acute infection with COVID-19, a certain proportion of recovered patients remained diffusion impairment, and patients who were more severely ill during their hospital stay had more severe impaired pulmonary diffusion capacities and abnormal chest imaging manifestation. 43 Therefore, it was likely that the erectile function in COVID-19 patients with a recovery time of 80 days was impaired.…”
Section: Discussionmentioning
confidence: 99%
“…To date, mounting evidence suggests that COVID-19 survivors may encounter long-term health issues [ 64 , 65 ]. Chronic unexplained medical symptoms of so called “long COVID” had been reported in both adults and children [ [66] , [67] , [68] , [69] , [70] ], even among initially mild-infected patients, which included fatigue, headache, insomnia, dizziness, lung damage, erectile dysfunction, as well as other psychiatric and neurological symptoms. In a recent cohort study of COVID-19 patients discharged from hospitals for 6 months, most survivors were still troubled by a number of symptoms, including fatigue or muscle weakness, sleep difficulties, anxiety or depression [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Sansone and colleagues in a study conducted on 100 patients, showed that 25 patients who were infected with SARS-CoV2 had a higher prevalence of ED than the 75 healthy patients who were not infected. Furthermore, regression analysis confirmed that COVID-19 has a significant effect on the development of ED independently of other variables affecting erectile function, such as psychological status, age, and BMI ( 109 ). This association is probably due to the detrimental effect of the disease on endothelial function, whose integrity is, in turn, fundamental for the erective mechanism.…”
Section: Endocrine Diseases and Covid-19mentioning
confidence: 74%